THE IMAGE OF PETER THE GREAT IN THE HISTORICAL MEMORY OF THE DAGESTAN POPULATION - Polcaeva, Fatimat Abdulnetifovna; Kasymov, Dzavid Ahmedoglu (History, Archeology and Ethnography of the Caucasus, 2020)
The Persian campaign of Peter I has been the subject of numerous studies, as well as his influence on Russia-Dagestan relations, social-economic and cultural development of the region. However, the question of the place of the Russian emperor in the historical memory of the population of Dagestan, which was largely influenced by the Persian campaign, remains unexplored. The present paper, basing on indirect material of written evidence and principles of historicism, taking into account regional features, attempts to recreate the image of Peter the Great. Having examined the events of the campaign in chronological order and applying common scientific methods of analysis, abstraction and inductive approach, the authors identified events and actions that are descriptive of the emperor’s personality. Determining the place of Peter I in the historical memory of the people of Dagestan, a concept of the French sociologist M. Halbwachs on “mnemonic sites” is used. In the course of the study, a number of such “sites of memory” were revealed on the territory of Dagestan associated with Peter I. The authors also consider some acts of commemoration, directed on preserving mnemonic places and the development of historical memory of the population.